Tim Nasional Sepak Bola Sebagai Instrumen Soft Power: Studi Kajian Strategis Atas Kebijakan Olahraga Indonesia - Mochammad Adham Syurya Mustahir Sidu (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This research analyzes the role of the Indonesian National Football Team as a soft power instrument in national sports policy. Utilizing Joseph Nye's theoretical framework of soft power, this qualitative study with a library research approach examines various programs and policies implemented by PSSI and the Indonesian government from the post-FIFA suspension in 2015 to the Erick Thohir leadership period. The findings indicate that football has transformed into an effective public diplomacy tool through three main pathways: enhancing national team performance through the naturalization of diaspora players of Indonesian descent, hosting international events such as the FIFA U-17 World Cup 2023, and developing sports infrastructure integrated with the National Sports Grand Design (Desain Besar Olahraga Nasional/DBON) policy. This study finds that the diaspora naturalization policy produces a dual impact: on one hand, it improves team competitiveness and fosters an inclusive image, while on the other hand, it triggers contestation over national identity. The contribution of this research is to present a strategic mapping of football utilization as soft power within the holistic framework of Indonesian national sports policy.